An Integrated Community-Based Human Resource Management Framework for Sustainable Economic Development: Insights from Indonesia - M. Irvanni Bahri; Roni Adi; Fatmaida Naila Ansori; Siti Nur Maulidina (International Journal of Management Science and Information Technology, 2026)
Human Resource Management (HRM) has become a strategic determinant of sustainable economic development amid globalization, digital transformation, and the transition toward a knowledge-based economy. Although previous studies have extensively examined the relationships between Human Resource Management, Human Capital, Community-Based Development (CBD), and Sustainable Economic Development (SED), these concepts have largely been investigated independently, resulting in limited understanding of their integrated role in promoting inclusive and sustainable development. This study aims to develop an integrated conceptual framework that explains how Human Resource Management contributes to Sustainable Economic Development through Human Capital Development and is strengthened by Community-Based Development within the Indonesian context. A conceptual research design was employed using a structured literature review approach. Relevant studies indexed in the Scopus database were systematically identified, screened, synthesized, and critically analyzed to establish conceptual relationships among the four constructs. The findings propose the Integrated Community-Based Human Resource Management Framework, which positions Human Resource Management as a strategic driver for developing Human Capital through competency development, lifelong learning, talent management, and capacity building. Community-Based Development functions as an enabling mechanism that transforms individual capabilities into collective capacity through participation, empowerment, collaboration, and institutional strengthening, ultimately contributing to productivity growth, innovation, competitiveness, social inclusion, and long-term sustainable economic development. The framework further highlights the dynamic interaction between Human Capital Development and Community-Based Development through a feedback mechanism influenced by contextual drivers, including digital transformation, institutional governance, public policy, and the Sustainable Development Goals (SDGs). This study contributes to the literature by integrating Human Resource Management, Human Capital, Community-Based Development, and Sustainable Economic Development into a unified conceptual framework that extends the role of Human Resource Management beyond organizational performance toward a development-oriented perspective. The proposed framework also provides strategic insights for policymakers, organizations, educational institutions, and community stakeholders in designing more inclusive and sustainable human resource development policies.